2007
DOI: 10.5650/jos.56.319
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Consumption of Alpha-Linolenic, Eicosapentaenoic and Docosahexaenoic Acids in Human Metabolic Syndrome and Type 2 Diabetes- A Mini-Review

Abstract: The human metabolic syndrome and its frequent sequela, type 2 diabetes are epidemic around the world. Alpha-linolenic acid (ALA, 18:3 n-3), eicosapentaenoic acid (EPA, 20:5 n-3) and docosahexaenoic acid (DHA, 22:6 n-3) consumption ameliorates some of these epidemics' features thus leading one to question if consumption of EPA and DHA, and their metabolic precursor ALA reduce the conversion of metabolic syndrome to type 2 diabetes and reduce the major cause of death in the metabolic syndrome and type 2 diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 57 publications
1
46
0
1
Order By: Relevance
“…There is some evidence that EPA and DHA consumption significantly benefits metabolic syndrome in terms of dyslipidemia, particularly hypertriglyceridemia 32) . In animal studies, various mechanisms have been reported: increased fatty acid oxidation in the liver 33) , inhibition of hormone-sensitive lipase and VLDL secretion, and increased lipoprotein lipase activity 34) .…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that EPA and DHA consumption significantly benefits metabolic syndrome in terms of dyslipidemia, particularly hypertriglyceridemia 32) . In animal studies, various mechanisms have been reported: increased fatty acid oxidation in the liver 33) , inhibition of hormone-sensitive lipase and VLDL secretion, and increased lipoprotein lipase activity 34) .…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanisms are still unknown, a recent paper reported that n-3 PUFA exerts a tissue-specific regulatory effect on phosphatidylinositol 3'-kinase, which acts as an important regulator of insulin signaling in rats 39) . In addition, inflammatory responses, including interleukin-6, tumor necrosis factor-, and adipocytokines, might be involved in the association between PUFA and insulin resistance 40) . In the present study, no significant associations in EPA/AA levels in serum or RBCs between subjects with and without MetS were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (2002) in a metaanalysis of nine cross-sectional studies found a significant inverse association between dietary protein and blood pressure in both genders. It has been suggested that potentially protein intake could influence arterial BP through the actions of its constituent amino acids (Ginsberg, 2000;Barre, 2007). In addition, insulin's role in hypertension may be somewhat more direct, with hyperinsulinemia potentially leading to salt and water retention (Storlien et al, 1996).…”
Section: Methodsmentioning
confidence: 99%